2010
DOI: 10.1007/s00439-010-0864-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple enhancers located in a 1-Mb region upstream of POU3F4 promote expression during inner ear development and may be required for hearing

Abstract: POU3F4 encodes a POU-domain transcription factor required for inner ear development. Defects in POU3F4 function are associated with X-linked deafness type 3 (DFN3). Multiple deletions affecting up to ~900-kb upstream of POU3F4 are found in DFN3 patients, suggesting the presence of essential POU3F4 enhancers in this region. Recently, an inner ear enhancer was reported that is absent in most DFN3 patients with upstream deletions. However, two indications suggest that additional enhancers in the POU3F4 upstream r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 26 publications
(57 reference statements)
2
33
0
Order By: Relevance
“…In recent years, numerous cis-regulatory regions of animal genes have been shown to contain multiple enhancers with overlapping or very similar expression patterns (Jeong et al, 2006;Werner et al, 2007;Hong et al, 2008;McGaughey et al, 2008;Corbo et al, 2010;Frankel et al, 2010;Kalay and Wittkopp, 2010;L'Honore et al, 2010;Naranjo et al, 2010;Perry et al, 2010Perry et al, , 2011Franchini et al, 2011;Galindo et al, 2011;Ghiasvand et al, 2011;Lee et al, 2011;McBride et al, 2011;Watts et al, 2011;Pauls et al, 2012). Yet, the first observations of overlapping expression from different enhancers date back from the 1990s (Hoch et al, 1990;Kassis, 1990;Tolias and Kafatos, 1990).…”
Section: Genes Have Multiple Enhancers With Overlapping or Very Similmentioning
confidence: 99%
“…In recent years, numerous cis-regulatory regions of animal genes have been shown to contain multiple enhancers with overlapping or very similar expression patterns (Jeong et al, 2006;Werner et al, 2007;Hong et al, 2008;McGaughey et al, 2008;Corbo et al, 2010;Frankel et al, 2010;Kalay and Wittkopp, 2010;L'Honore et al, 2010;Naranjo et al, 2010;Perry et al, 2010Perry et al, , 2011Franchini et al, 2011;Galindo et al, 2011;Ghiasvand et al, 2011;Lee et al, 2011;McBride et al, 2011;Watts et al, 2011;Pauls et al, 2012). Yet, the first observations of overlapping expression from different enhancers date back from the 1990s (Hoch et al, 1990;Kassis, 1990;Tolias and Kafatos, 1990).…”
Section: Genes Have Multiple Enhancers With Overlapping or Very Similmentioning
confidence: 99%
“…Distal enhancers can regulate their target genes from long distances, the most extreme case being the Shh gene’s enhancer at ∼1 Mb away, and are especially important in regulating critical developmental genes (3,4). Recent advances in sequencing technologies have revealed that cell-specific enhancers are often marked by P300 binding (a histone acetyltransferase and transcription coactivator) (5,6), as well as other epigenomic marks such as DNAse hypersensitivity (DHS), H3K4me1, H3K27ac and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…3, 1820 However, it is difficult to detect such large genomic alterations using conventional PCR-based DNA sequencing. Anger et al have reported normal genetic sequencing results in a DFNX2 case with chromosomal rearrangements in the vicinity of POU3F4 , suggesting a failure of Sanger sequencing to identify mutations because of genetic causes.…”
Section: Discussionmentioning
confidence: 99%